PELATIHAN STRATEGI “HYPONYM MAPPING” TERHADAP PENGUASAAN RELASI MAKNA KOSAKATA BAHASA INGGRIS SISWA MTS DARURRAHMAN NW SELONG LOMBOK TIMUR - Terasne Terasne; Ahmad Hanan; Baiq Sumarni; Baiq Zuhrotun Nafisah (LPPM Institut Pendidikan Nusantara Global, 2025)
Vocabulary mastery was considered a fundamental aspect of English learning, yet many students struggled to understand semantic relationships. This community service activity aimed to improve vocabulary mastery and the ability to organize hypernym–hyponym relations using the Hyponym Mapping strategy. Thirty second-grade students of MTs Darurrahman NW Selong, East Lombok, participated. The implementation included a pre-test, interactive training through the Hyponym Chain Game and concept map creation, and a post-test. The results showed that the average pre-test score of 61.83 increased to 82.67 in the post-test; the average N-Gain was 0.56 (56.26%), categorized as moderately effective. Qualitative analysis indicated that students were able to construct hierarchical concept maps and identify hypernym–hyponym relations. It was concluded that Hyponym Mapping was effective in improving vocabulary mastery and semantic understanding and feasible for sustained classroom use.